Otimização de protocolos de criopreservação do sêmen de catetos (Pecari tajacu LINNEAUS, 1758) - Souza, Ana Liza Paz (Universidade Federal Rural do Semi-Árido, 2015)
The present thesis had as objective optimized peccaries semen cryopreservation protocols (Pecari tajacu). Therefore, adult animals were used originated from the Multiplication Center of Wild Animals (CEMAS) of the Federal Rural University of the Semi-Arid (UFERSA), which semen was collected by electroejaculation and immediately evaluated. The first experiment aimed at evaluating the effect of low-density lipoprotein (LDL) purified in relation to egg yolk (G) and defines the ideal concentration (20%, 10% and 5%) for semen cryopreservation in peccaries. After the data analysis it was found that LDL (20%) can be used to replace egg yolk having been verified 36.4 ± 5.3 and 21.8 ± 6.9% of the total sperm motility after thawing, respectively. The second experiment evaluated the action of Aloe vera gel (AV) both refrigeration and in the peccaries of semen freezing in different concentrations (20%, 10%, 5%) or associated with egg yolk (10%:10%). It was found that Aloe vera gel (20%) proved to be efficient cooling at 5 ° C, maintaining the longevity of sperm for up to 48 hours of total motility assessment having a 54.2 ± 21.3%; as the cryopreservation process, it was found that the use of Aloe vera 20% can replace egg yolk, but its association with gem promoted better preservation of viability (32.7 ± 2.3%), osmotic response (37.8 ± 4.2%) and membrane integrity (40.2 ± 3.1). In the third experiment evaluated the addition of the action (0.5% and 1.0%) of base detergent sodium dodecyl sulfate (SDS), Equex ® STM, the peccaries of semen. However, it was observed that, at any concentration proposal was effective in increasing the longevity of sperm cell peccaries over 15 minutes as previously described for the species. The experiments have been sufficient to answer the hypotheses and are useful for the improvement of semen cryopreservation protocols of collared peccary (Pecari tajacu)
Cryopreservation protocols optimization of semen collared peccaries (Pecari tajacu Linneaus, 1976)
Keywords: peccary; Aloe vera; cryopreservation; Dodecyl Sulfate sodium; Low Density sulfate; Cateto; Aloe vera; Criopreservação; Dodecil Sulfato de Sódio; Lipoproteína de Baixa Densidade; CIENCIAS AGRARIAS::MEDICINA VETERINARIA